Front Cover: Autotransporter Adhesins in Escherichia coli Pathogenesis. Issue 23 (20th December 2017) - Vo, Julieanne L.; Martínez Ortiz, Gabriela Constanza; Subedi, Pramod; Keerthikumar, Shivakumar; Mathivanan, Suresh; Paxman, Jason J.; Heras, Begoña
Abstract : DOI:10.1002/pmic.201600431 Autotransporter proteins are the largest family of secreted proteins in Gram‐negative bacteria. As discussed in article number 1600431 by Julieanne L. Vo et al., this family includes outer membrane adhesins and secreted serine proteases, which promote virulence functions such as adhesion and invasion of host cells, biofilm formation and cytotoxicity. Autotransporters incorporate a membrane spanning beta‐barrel and an extracellular functional domain. This figure represents the architecture of a trimeric adhesin (YadA (1P9H, 3H7X, 2LME)); a beta‐helical adhesin (Antigen 43 functional domain and AIDA‐I beta‐barrel (4KH3, 4MEE)) and a serine protease autotransporter (Hemoglobin‐binding protease (1WXR, 3AEH)).